Cognitive abilities and medical students' practice of physical exams: A quasi-experimental study - Yamamoto, Lucas Moura; Pavin, Matheus Landi; Souza, Giordano Bruno Duarte de; Oliveira, Julio Lamartine Hayne Bastos de; Costa, Raphael Raniere de Oliveira; Fernandes, Adriano Yacubian [UNESP]; Mazzo, Alessandra (Associacao Paulista Medicina, 2023)
BACKGROUND: To highlight the importance of clinical simulations and simulated laboratories for studentOBJECTIVE: To evaluate the gains obtained by medical students in their cognitive and practical performance of physical examinations (abdominal, cardiological, and pulmonary), as well as satisfaction and self-confidence in what they have learned, after concentrated practice developed in a skills and simulation laboratory.DESIGN AND SETTING: A quantitative and quasi-experimental study in which 48 students were evaluatMETHODS: A quantitative and descriptive study was conducted with regularly enrolled 2nd year medical students over 18 years of age who had content prior to data collection regarding anamnesis and physical examination remotely taught in a Moodle virtual learning environment. For data collection, the participants were subjected to a concentrated period of skill training (abdominal, cardiological, and pulmonary). Every day after the skill training session, they were subjected to a practical evaluation and completed a theoretical test before and after the practical activities. At the end of all activities, they answered the instrument to assess the simulated practices (self-confidence and satisfaction).RESULTS: Among the 49 students evaluated, positive and significant theoretical and practical gains were identified in all three components (abdominal, cardiological, and pulmonary) (P = 0.000), as well as in the general evaluation (Theoretical 1 and Theoretical 2) (P = 0.000), satisfaction, and self-confidence (P = 0.000). CONCLUSION: Concentrated laboratory practice resulted in positive improvements in students' physical examination skills.
Keywords: Physical examination; Students medical; Education; medical; Self-concept